Pengaruh Likuiditas Terhadap Nilai Perusahaan Melalui Struktur Modal Dan Profitabilitas - Ratna Uli; Wawan Ichwanudin; Emma Suryani (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aimed to determine the effect of variable liquidity on firm value with capital structure and profitability as an intervening variable in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2013-2017. In this study the liquidity variable was proxied by the current ratio, the capital structure was proxied by the debt to equity ratio, profitability was proxied by return on assets and the firm value was proxied by price book value. The sample used in this study was 15 companies in the food and beverage sub-sector listed on the Indonesia stock exchange for the period 2013-2017. The data analysis method used in this study was the causal step method, and data testing was done with the help of SPSS 22 software. The results of this study indicated that (1) liquidity had a positive and significant effect on firm value, (2) liquidity had a negative and significant effect on capital structure, (3) capital structure had no effect on firm value, (4) liquidity did not affect profitability, (5) profitability had a positive and significant effect on firm value, (6) capital structure was not able to mediate the effect of liquidity on firm value, (7) profitability was not able to mediate the effect of liquidity on firm value